The McGill Transgenic Rat Model of Alzheimer's Disease Displays Cognitive and Motor Impairments, Changes in Anxiety and Social Behavior, and Altered Circadian Activity - Petrasek, Tomas; Vojtechova, Iveta; Lobellova, Veronika; Popelikova, Anna; Janikova, Martina; Brozka, Hana; Houdek, Pavel; Sladek, Martin; Sumova, Alena; Kristofikova, Zdenka; Vales, Karel; Stuchlík, Ales (Frontiers in Aging Neuroscience, 2018)
The McGill-R-Thy1-APP transgenic rat is an animal model of the familial form of Alzheimer’s disease (AD), mirroring many neuropathological hallmarks of the disease and gradual deterioration of cognitive functions. In this study, we describe thorough characterization of the model in several domains. On the behavioral level, we report normal locomotor activity in spontaneous exploration, but problems with balance or gait coordination, increased anxiety and severely impaired spatial cognition in 4 - 7 months old animals. The profile of social behavior and ultrasonic communication is altered in the McGill rats, without a general social withdrawal. McGill rats also exhibit changes in circadian profile, with shorter free-running period and increased total activity during subjective night, without signs of sleep disturbances during the inactive phase. Expression of circadian clock gene Bmal1 was found to be increased in the parietal cortex and cerebellum, while Nr1d1 expression was not changed. The clock-controlled gene Prok2 expression was found to be elevated in the parietal cortex and hippocampus, which might contribute to the observed changes in circadian phenotype. We conclude that the AD-like phenotype in the rat model is not restricted to cognitive domain, but also includes gait problems, changes in emotionality, social behavior and circadian profiles, paralleling the spectrum of symptoms observed in human patients and enabling development of new therapeutic approaches targeting not only memory decline but also other symptoms decreasing the quality of life of the patients.